Application of Fuzzy - AHP - Topsis in Online Shopping Selection On B2C E-Commerce Websites - Trung Dung, Tran; Minh Hai, Le Thi; Tra My, Hoang; Hoang Mai, Nguyen; Khanh Linh, Cao Ha (International Journal of Scientific Research and Management (IJSRM), 2024)
In today's digital age, online shopping is not only a trend but also an indispensable part of our daily lives. With the convenience and diversity of e-commerce websites, consumers can easily experience and choose goods and services from all over the world in just a few clicks. However, making online shopping decisions is not always easy. Consumers often have to face a number of factors such as price, product quality, brand, after-sales service, delivery time and many other factors, as well as facing uncertainty and ambiguity in the information. reviews. To help users choose products effectively, the Fuzzy - AHP - Topsis integration model has been applied in this research topic to propose evaluation criteria for choosing to buy products on 4 B2C websites including Shopee, Tiki, Lazada, Sendo.